Estudo do comportamento de solos através de ensaios de placa de diferentes diâmetros - Russi, Daniel (2007)
The dimensioning of shallow foundations requires the professional to define clearly and objectively, for the soil in question, the load capacity and forecast the settlings of the foundation submitted to the structure having as base its mechanical properties obtained through field and/or laboratory investigation. One of the safest ways to take this decision is based on information from plate load tests because through this it is possible to reproduce in a minor proportion the real behavior of the future foundation, perhaps using this as a tool to help in the decision making to dimension shallow foundations, contributing to a more efficient development of the foundation work. The present work is about the analysis of the CEEG/UFSM soil behavior through tests on direct load proof on foundation field (plate load test). The research is divided, basically into two great phases. There was an experimental phase which comprehended geotechnical characterization trials and plate load tests to evaluate the behavior tension-settling of foundation. There were 7 plate load tests in 3 ditches dug manually up to 0,7 m depth. Plates with 15, 30 and 50 cm diameter were used and the reaction system was formed by reaction piles united by a reaction beam. The second phase was the analysis of the results obtained, analyzed through curves tension-settling of foundation, where some criteria were applied to define the rupture tension and some considerations were done on the settling of foundation forecast and scale effect.